A review of mechanisms and models for dynamic failure, strength, and fragmentation. (March 2015) - Ramesh, K.T.; Hogan, James D.; Kimberley, Jamie; Stickle, Angela
Abstract: Modeling of catastrophic disruption requires understanding the processes of dynamic failure and fragmentation. This paper summarizes current mechanisms and models for dynamic failure, strength, and fragmentation, reviewing these from a mechanics perspective and with an emphasis on making links to the developing advances in these areas in the engineering and computational mechanics communities. We describe dynamic failure processes, examine size and rate effects, articulate the scaling concepts that arise naturally from these processes, and examine the influences of these processes on effective strength and fragmentation. Abstract : Highlights: Summarizes mechanisms for dynamic failure, strength, and fragmentation, reviewing these from a mechanics perspective. Emphasis on making links to the developing advances in these areas in the engineering and computational mechanics communities.